Fluorine-free transparent super-hydrophobic coating as well as preparation method and application thereof

By using TeOS and BPH-8 and other materials to prepare fluorine-free transparent ultra-hydrophobic coating, solve the problem of complex existing craftsmanship and fluoride, and achieve efficient, environmentally friendly transparent ultra-hydrophobic coating preparation. Light performance.

CN119331441AActive Publication Date: 2025-01-21JILIN UNIVERSITY +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411450647.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing transparent superhydrophobic coating process is complex and requires the use of fluoride, resulting in high production costs and pollution to health and the environment.

Method used

Use silicate ethyl ester (TEOS) as the front of the silicon dioxide, obtains silico-soluble through hydrolysis-shrinkage, and mixes with the BPH-8 gel factor to form a composite dry gel coating. Cincin Sillorilane is hydrophobic and modified to obtain fluoride, transparent ultra -hydrophobic coating.

Benefits of technology

The preparation of fluorine-free transparent super-hydrophobic coating is achieved, which has excellent hydrophobicity and light transmittance, with a water contact angle of 162.7°, an average visible light transmittance of 84.8%, and good self-cleaning ability, reducing production costs. Avoid pollution to health and environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331441A_ABST
    Figure CN119331441A_ABST
Patent Text Reader

Abstract

The invention provides a fluoride-free transparent super-hydrophobic coating as well as a preparation method and application thereof, and belongs to the technical field of coating materials. A three-dimensional network structure formed by self-assembly of bisamide derivatives (1, 4-bis [(3, 4-dioctyloxyphenyl)-bisamide] benzene and BPH-8) is used as a template, TEOS (tetraethyl orthosilicate) is used as a silicon dioxide precursor to be adsorbed on the surface of the template for sol-gel polymerization to form silicon dioxide with high transparency, then BPH-8 is removed through calcination, and the high-transparency silicon dioxide is obtained. And performing hydrophobic modification on the silicon dioxide surface by using octyl trichlorosilane to obtain the transparent super-hydrophobic coating. The water contact angle of the prepared fluorine-free transparent super-hydrophobic coating can reach 162.7 degrees, the rolling angle is smaller than 3 degrees, the average transmittance of visible light is 84.8%, and the fluorine-free transparent super-hydrophobic coating has good self-cleaning capacity and has potential application value in the fields of building glass, vehicle window glass, rearview mirrors, optical lenses, solar photovoltaics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating materials, and in particular to a fluorine-free transparent super-hydrophobic coating and a preparation method and application thereof. Background Art

[0002] People can see many special wetting phenomena in nature, such as lotus leaves, butterfly wings, shark skin, etc., whose surfaces have excellent waterproof properties. People call this surface with a contact angle of more than 150° and a rolling angle of less than 10° with water droplets a super-hydrophobic surface. Super-hydrophobic surfaces have a variety of functional properties, such as self-cleaning, anti-fouling, oil-water separation, anti-corrosion, etc., and can be widely used in daily life and industrial fields. However, for optical materials or electronic devices with high requirements for transparency, such as architectural glass, car window glass, rearview mirrors, optical lenses, solar panels, etc., due to frequent exposure to the outdoors, the environment is easily polluted, which will reduce its transparency and affect its working performance. For such applications, it is necessary to combine transparency with super-hydrophobicity, so that it can maintain self-cleaning and anti-fouling properties under the premise of transparency, so the development of a transparent super-hydrophobic coating has great application prospects.

[0003] The construction of super-hydrophobic coating usually needs to meet two conditions, that is, the surface has a certain rough structure and low surface free energy. From the perspective of surface roughness, rough structure can affect visible light transmittance, so the preparation of transparent super-hydrophobic coating requires surface roughness so as to balance between super-hydrophobicity and transparency. At present, people have prepared various transparent super-hydrophobic coatings by various methods such as vapor deposition, etching, electrochemical deposition, sol-gel method, template method, such as the Chinese patent of publication number CN115849295A first utilizes phase separation technology, dry etching and vacuum evaporation, and disordered nanopore structure is prepared on silicon substrate, and then the disordered nanopore structure on silicon substrate is copied to quartz glass substrate by ultraviolet nanoimprinting technology, and finally vacuum evaporation, dry etching and use fluoroalkyl chlorosilane to carry out low surface energy treatment to obtain transparent super-hydrophobic coating. The Chinese patent with publication number CN116535585A first uses glycidyl acrylate and perfluoropolyether acrylate to prepare fluorinated epoxy acrylate polymer through free radical polymerization, then uses nano-silica, tridecafluorooctyl triethoxysilane and γ-glycidyloxypropyl triethoxysilane to prepare fluorinated silica dispersion, and finally the fluorinated epoxy acrylate polymer, fluorinated silica dispersion and epoxy resin are compounded for coating, and the coating is cured by ultraviolet light to obtain a transparent super hydrophobic coating.

[0004] However, most of these methods have problems such as complex processes, the need for specialized equipment and the use of fluorides, which significantly increase production costs. In addition, fluorides are not easily degradable and can easily cause health and environmental problems. Summary of the invention

[0005] The object of the present invention is to provide a fluorine-free transparent super hydrophobic coating and a preparation method and application thereof. The super hydrophobic coating has good transmittance in the visible light region and does not use fluorine-containing materials, thereby reducing pollution to health and the environment. In addition, the present invention also solves the problem of complex process of existing super hydrophobic coatings and reduces production costs.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a fluorine-free transparent super-hydrophobic coating, comprising the following steps:

[0008] Tetraethyl silicate, an organic solvent and an acid solution are mixed and subjected to hydrolysis-condensation to obtain a silica sol;

[0009] The silica sol is mixed with the BPH-8 gel factor under heating conditions, the obtained hot sol is coated on a substrate, and then dried to obtain a composite xerogel coating;

[0010] calcining the composite xerogel coating to obtain a calcined coating;

[0011] The calcined coating is immersed in a modifier solution to modify the coating to obtain a fluorine-free transparent super hydrophobic coating;

[0012] The modifier in the modifier solution includes n-octyltrichlorosilane.

[0013] Preferably, the acid solution comprises hydrochloric acid; the mass concentration of the acid solution is 7.5-10%.

[0014] Preferably, the organic solvent comprises ethanol; the usage ratio of tetraethyl silicate to the organic solvent is 3-30 mg:10 mL; the usage ratio of tetraethyl silicate to the acid solution is 3-30 mg:0.4 mL.

[0015] Preferably, the hydrolysis-condensation temperature is 10-30° C. and the time is 2-3 hours.

[0016] Preferably, the usage ratio of the silica sol to the BPH-8 gel factor is 10-11 mL:20 mg.

[0017] Preferably, the silica sol and the BPH-8 gel factor are mixed at a temperature of 160 to 170° C. and a time of 120 to 300 seconds.

[0018] Preferably, the calcination temperature is 500-600° C. and the calcination time is 2-3 hours.

[0019] Preferably, the concentration of the modifier solution is 2-5 wt %; the modification temperature is 10-30° C., and the modification time is 2-3 h.

[0020] The present invention provides a fluorine-free transparent super hydrophobic coating prepared by the preparation method described in the above technical solution.

[0021] The present invention provides the application of the fluorine-free transparent super-hydrophobic coating described in the above technical solution in the field of architectural glass, vehicle window glass, rearview mirror, optical lens or solar photovoltaic.

[0022] The present invention provides a method for preparing a fluorine-free transparent super-hydrophobic coating. The present invention uses tetraethyl silicate (TEOS) as a silica precursor, obtains a silica sol by hydrolysis-polycondensation, and then dissolves BPH-8 in a heated silica sol, and the resulting hot sol is uniformly coated on a substrate, and after cooling, BPH-8 self-assembles to form a three-dimensional mesh structure, and TEOS is adsorbed on the fiber surface and undergoes polymerization reaction, and finally forms a composite gel coating; Subsequently, the solvent evaporates to obtain a dry gel coating, and BPH-8 is removed by calcination to obtain a fibrous silica transparent surface. Then, octyl trichlorosilane is reacted with the silica surface hydroxyl group for hydrophobic modification to obtain a transparent super-hydrophobic coating. The super-hydrophobic coating prepared by the present invention has excellent hydrophobicity and light transmittance, and the contact angle with water can reach 162.7°, the rolling angle is less than 3°, the average visible light transmittance is 84.8%, and it has good self-cleaning ability.

[0023] The preparation process of the present invention is simple, and the prepared coating does not contain any fluoride, which solves the problems of complex process and use of fluoride in existing super-hydrophobic coatings, has low cost, does not require sophisticated equipment, and is environmentally friendly (fluoride is not easily degraded and easily causes environmental problems). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the schematic diagram of TEOS hydrolysis-condensation reaction;

[0025] Figure 2 This is the principle diagram of n-octyltrichlorosilane modification;

[0026] Figure 3 The transparency display effect photos of the coatings prepared in Examples 1 to 5;

[0027] Figure 4 is the contact angle of the coating prepared in Examples 1 to 5;

[0028] Figure 5 The transparency test results of the coatings prepared in Examples 1 to 5;

[0029] Figure 6Scanning electron micrographs of coatings prepared with different TEOS concentrations; wherein (a) TEOS concentration is 0.3 mg / mL, (b) TEOS concentration is 1.0 mg / mL, (c) TEOS concentration is 1.5 mg / mL, (d) TEOS concentration is 2.0 mg / mL, and (e) TEOS concentration is 3.0 mg / mL;

[0030] Figure 7 The self-cleaning ability test results of the coating prepared in Example 1 and the untreated glass substrate are shown in FIG. 1 , wherein (a) is the untreated glass substrate, and (b) is the coating prepared in Example 1;

[0031] Figure 8 The wetting conditions of different liquids on the coating surface prepared in Example 1. DETAILED DESCRIPTION

[0032] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0033] The present invention provides a method for preparing a fluorine-free transparent super-hydrophobic coating, comprising the following steps:

[0034] Tetraethyl silicate, an organic solvent and an acid solution are mixed and subjected to hydrolysis-condensation to obtain a silica sol;

[0035] The silica sol is mixed with the BPH-8 gel factor under heating conditions, the obtained hot sol is coated on a substrate, and then dried to obtain a composite xerogel coating;

[0036] calcining the composite xerogel coating to obtain a calcined coating;

[0037] The calcined coating is immersed in a modifier solution to modify the coating to obtain a fluorine-free transparent super hydrophobic coating;

[0038] The modifier in the modifier solution includes n-octyltrichlorosilane.

[0039] In the present invention, the acid solution preferably includes hydrochloric acid; the mass concentration of the acid solution is preferably 7.5-10%, more preferably 7.5-8.0%.

[0040] In the present invention, the organic solvent preferably includes ethanol; the usage ratio of tetraethyl silicate to the organic solvent is preferably 3-30 mg:10 mL, more preferably 15 mg:10 mL.

[0041] In the present invention, the dosage ratio of tetraethyl silicate (TEOS) to the acid solution is preferably 3-30 mg:0.4 mL, 15 mg:0.4 mL. TEOS is a precursor for forming silicon dioxide, and the surface structure of the silicon dioxide coating after calcination is controlled by adjusting the dosage of TEOS to ensure the hydrophobicity and transparency of the coating.

[0042] In the present invention, tetraethyl silicate is preferably added to an organic solvent, and magnetically stirred for 10 minutes to obtain a tetraethyl silicate solution, and an acid solution is added to perform hydrolysis-condensation under magnetic stirring to obtain a silica sol.

[0043] In the present invention, the hydrolysis-condensation temperature is preferably 10-30° C., more preferably 25° C., and the time is preferably 2-3 hours, more preferably 2 hours. The present invention has no particular limitation on the stirring, and the stirring can be carried out according to a process well known in the art.

[0044] The present invention carries out hydrolysis-condensation under acid catalysis conditions (principle see Figure 1 ) to obtain a silica sol containing TEOS hydrolysis condensation products.

[0045] After the hydrolysis-condensation is completed, the present invention preferably does not require post-treatment and directly mixes the obtained silica sol with the BPH-8 gel factor.

[0046] In the present invention, the BPH-8 gel factor is 1,4-di[(3,4-dioctyloxyphenyl)-biphenylamide]benzene prepared according to the method described in patent CN 105858592A, and its structural formula is:

[0047]

[0048] In the present invention, the mass ratio of the silica sol to the BPH-8 gel factor is preferably 10-11 mL:20 mg, and more preferably 10.4-10.6 mL:20 mg.

[0049] In the present invention, the temperature for mixing the silica sol and the BPH-8 gel factor is preferably 160-170° C., more preferably 160° C., and the time is preferably 120-300 s, more preferably 150-240 s.

[0050] The present invention preferably adds the BPH-8 gel factor into the silica sol, heats and dissolves it, and then coats it on a glass substrate. After drying in a ventilated place for 12 hours, a BPH-8 / SiO2 composite dry gel coating is obtained.

[0051] The present invention has no particular limitation on the glass substrate, and any corresponding substrate known in the art may be used.

[0052] The present invention uses the three-dimensional network structure formed by BPH-8 as a template to induce the acid-catalyzed TEOS hydrolysis-condensation product to polymerize on the template surface to form fibrous silica. The transparent super-hydrophobic coating can be prepared by adjusting the amount of TEOS used to control the size of the nano-micron structure and balancing the contradiction between the transparency of the coating and the hydrophobicity of the structure (super-hydrophobicity requires the surface to have high roughness, while high roughness will cause light scattering, thereby reducing transparency).

[0053] In the present invention, the calcination temperature is preferably 500-600° C., the calcination time is preferably 2-3 hours, more preferably 2 hours. During the calcination process, the organic BPH-8 component is removed, leaving only the silicon dioxide structure on the surface.

[0054] In the present invention, the modifier in the modifier solution includes n-octyltrichlorosilane; the concentration of the modifier solution is preferably 2-5wt%, more preferably 3wt%; the solvent used in the modifier solution is preferably n-hexane. During the modification of the present invention, the calcined coating is completely immersed in the modifier solution; the amount of the modifier is determined by the modification time and the concentration of the modifier solution.

[0055] In the present invention, the modification temperature is preferably 10 to 30° C., more preferably 25° C., and the modification time is preferably 2 to 3 hours, more preferably 2 hours.

[0056] like Figure 2 As shown, during the modification process, the chlorine group in n-octyltrichlorosilane reacts with the hydroxyl group on the surface of the coated silica, the hydrophilic hydroxyl group on the coating surface is greatly reduced, while the hydrophobic octyl group is increased, the silica is modified, and the hydrophobic property of the coating surface is improved.

[0057] After the modification, the present invention preferably washes the obtained product with ethanol and then dries it to obtain a fluorine-free transparent super hydrophobic coating.

[0058] The present invention provides a fluorine-free transparent super hydrophobic coating prepared by the preparation method described in the above technical solution.

[0059] The present invention provides the application of the fluorine-free transparent super hydrophobic coating in the above technical solution in the field of architectural glass, vehicle window glass, rearview mirror, optical lens or solar photovoltaic. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0061] Example 1

[0062] (1) 15 mg of tetraethyl silicate (TEOS) was added to 10 mL of ethanol and magnetically stirred for 10 min to obtain an ethanol solution with a TEOS concentration of 1.5 mg / mL, and then 0.4 mL of a 7.5 wt% aqueous hydrochloric acid solution was added and magnetically stirred at 25° C. for 2 h to obtain a silica sol;

[0063] (2) adding 20 mg of 1,4-bis[(3,4-dioctyloxyphenyl)-biphenylamide]benzene (BPH-8) gel factor to 10.416 mL of silica sol prepared above, heating to 160°C to dissolve, mixing for 240 seconds, coating the obtained hot sol on a glass substrate to form an organic gel coating, and after ventilation drying for 12 hours, obtaining a BPH-8 / SiO2 composite dry gel coating;

[0064] (3) The obtained composite dry gel coating glass was calcined at 500°C for 2 h, and the obtained product was immersed in a hexane solution containing 3 wt% n-octyltrichlorosilane at 25°C for 2 h. The obtained product was washed with ethanol and dried to obtain a fluorine-free transparent super hydrophobic coating.

[0065] Example 2

[0066] The difference from Example 1 is that the amount of TEOS is adjusted to 3 mg, and the super-hydrophobic coating is prepared with an ethanol solution with a TEOS concentration of 0.3 mg / mL.

[0067] Example 3

[0068] The difference from Example 1 is that the amount of TEOS is adjusted to 10 mg, and the super-hydrophobic coating is prepared with an ethanol solution with a TEOS concentration of 1.0 mg / mL.

[0069] Example 4

[0070] The difference from Example 1 is that the amount of TEOS is adjusted to 20 mg, and the super-hydrophobic coating is prepared with an ethanol solution with a TEOS concentration of 2.0 mg / mL.

[0071] Example 5

[0072] The difference from Example 1 is that the amount of TEOS is adjusted to 30 mg, and the super-hydrophobic coating is prepared with an ethanol solution with a TEOS concentration of 3.0 mg / mL.

[0073] Test Example 1

[0074] Figure 3 The transparency display effect photos of the super hydrophobic coatings prepared in Examples 1 to 5; Figure 3 As shown, with the increase of TEOS concentration, the transparency of the coating gradually decreased and the word "superhydrophobic" under the coating became blurred.

[0075] The contact angles of the coatings prepared in Examples 1 to 5 were measured. The test results are shown in Figure 4 ,Depend on Figure 4 It can be seen that the wettability of the coating will change with the change of TEOS concentration. When the TEOS concentration is 0.3 mg / mL, the water contact angle of the coating is 123.2°. As the TEOS concentration increases, the water contact angle of the coating gradually increases. When the TEOS concentration increases to 1.5 mg / mL, the water contact angle of the coating increases to 162.7°. Then, as the TEOS concentration increases, the water contact angle gradually decreases. When the TEOS concentration is 3.0 mg / mL, the water contact angle is 156.3°. The above results show that when the TEOS concentration is 1.5 mg / mL, the coating has the best hydrophobicity. This is because as the TEOS concentration increases, the surface roughness of the coating also increases, thereby increasing the contact angle. However, when the TEOS concentration is too high, the surface structure of the coating changes, which reduces the contact angle.

[0076] Test Example 2

[0077] The transparency of the samples was tested using a UV-visible spectrophotometer, with the test light wavelength ranging from 400 to 780 nm, and the visible light transmittance of the coatings prepared in Examples 1 to 5 was measured. Figure 5 ,Depend on Figure 5 It can be seen that: with the increase of TEOS concentration, the visible light transmittance of the coating gradually decreases. The average transmittances of samples prepared with TEOS concentrations of 0.3 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, and 3.0 mg / mL are 87.9%, 86.0%, 84.8%, 77.7%, and 71.1%, respectively. This is because when the TEOS concentration is low, the surface roughness of the coating formed is small and the degree of light scattering is low, so the coating has higher transparency. With the increase of TEOS concentration, the surface roughness of the coating gradually increases, and the light scattering caused becomes more and more serious, and then the visible light transmittance of the coating will decrease.

[0078] Test Example 3

[0079] The coatings prepared in Example 1 and Example 2 were tested by scanning electron microscope. The test results are shown in Figure 6 .

[0080] Figure 6 , (a) TEOS concentration is 0.3 mg / mL, (b) TEOS concentration is 1.0 mg / mL, (c) TEOS concentration is 1.5 mg / mL, (d) TEOS concentration is 2.0 mg / mL, and (e) TEOS concentration is 3.0 mg / mL.

[0081] like Figure 6As shown in (a), when the TEOS concentration is 0.3 mg / mL, the coating surface morphology is relatively flat, with only a few protruding structures on the surface. When the concentration increases to 1.0 mg / mL, Figure 6 As shown in (b), a single layer of fibers appeared on the coating surface. When the concentration increased to 1.5 mg / mL, Figure 6 As shown in (c), the surface morphology of the coating changes into a multi-layer bundle fiber structure. When the concentration is 2.0 mg / mL, Figure 6 As shown in (d), it can be found that there are still many block structures on the fiber surface. When the concentration continues to increase to 3.0 mg / mL, as shown in Figure 6 As shown in (e), due to the excessive amount of TEOS, the bundled fibers on the coating surface are mostly transformed into a lamellar structure, and there are also deep cracks.

[0082] Test Example 4

[0083] In practical applications, super-hydrophobic coatings are exposed to the air and often come into contact with dust or liquids. The self-cleaning property of super-hydrophobic coatings makes it difficult for pollutants to adhere to their surface, and surface pollutants can be easily removed by aqueous solutions. Therefore, the self-cleaning ability of ordinary glass (sailing brand slide 7101) and the coating prepared in Example 1 was tested. Carbon black was placed on the sample surface as a pollutant, and then the sample was tilted and water droplets were dropped from above to observe the self-cleaning performance of the test sample. The test results are shown in Figure 1. Figure 7 , wherein (a) is an untreated glass substrate and (b) is the coating prepared in Example 1.

[0084] Test results for ordinary glass can be found in Figure 7 In (a), after adding water drops, due to the strong adhesion of ordinary glass to water, the water drops adhere to its surface and cannot effectively remove surface pollutants; the test results of the coating prepared in Example 1 are shown in Figure 7 In (b), after adding water droplets, due to the ultra-low adhesion of the super-hydrophobic surface to water, the water droplets roll rapidly on the coating surface and carry away the surface pollutants, leaving traces, indicating that the coating prepared in Example 1 has good self-cleaning ability.

[0085] Test Example 5

[0086] Take 20 μL of liquid and drop it on the surface of the coating prepared in Example 1, observe the state of the droplet on the surface of the coating, and test the wetting of different liquids (water (0.1wt% methylene blue aqueous solution), acid (0.1mol / L HCl solution), alkali (0.1mol / LNaOH solution), juice (Huiyuan), cola (Coca-Cola), coffee, Luckin Coffee) on the surface of the coating prepared in Example 1. The results are shown in Figure 8 .

[0087] Figure 8The wetting conditions of various liquids on the coating surface prepared in Example 1 are as follows: Figure 8 As shown, the various droplets tested showed regular spherical shapes on the coating surface, indicating that the coating has good repellency to these liquids and excellent hydrophobic effect.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a fluorine-free transparent super-hydrophobic coating, characterized in that: The following steps are involved: Tetraethyl silicate, an organic solvent and an acid solution are mixed and subjected to hydrolysis-condensation to obtain a silica sol; The silica sol is mixed with the BPH-8 gel factor under heating conditions, the obtained hot sol is coated on a substrate, and then dried to obtain a composite xerogel coating; calcining the composite xerogel coating to obtain a calcined coating; The calcined coating is immersed in a modifier solution to modify the coating to obtain a fluorine-free transparent super hydrophobic coating; The modifier in the modifier solution includes n-octyltrichlorosilane.

2. The preparation method according to claim 1, characterized in that: The acid solution includes hydrochloric acid; the mass concentration of the acid solution is 7.5-10%.

3. The preparation method according to claim 1 or 2, characterized in that: The organic solvent includes ethanol; the usage ratio of tetraethyl silicate to the organic solvent is 3-30 mg:10 mL; the usage ratio of tetraethyl silicate to the acid solution is 3-30 mg:0.4 mL.

4. The preparation method according to claim 3, characterized in that: The temperature of the hydrolysis-condensation is 10-30° C., and the time is 2-3 hours.

5. The preparation method according to claim 1, characterized in that: The dosage ratio of the silica sol to the BPH-8 gel factor is 10-11 mL: 20 mg.

6. The preparation method according to claim 1 or 5, characterized in that: The silica sol and the BPH-8 gel factor are mixed at a temperature of 160 to 170° C. and a time of 120 to 300 seconds.

7. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-600° C. and the calcination time is 2-3 hours.

8. The preparation method according to claim 1, characterized in that: The concentration of the modifier solution is 2-5wt%; the modification temperature is 10-30°C and the modification time is 2-3h.

9. A fluorine-free transparent super hydrophobic coating prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the fluorine-free transparent super hydrophobic coating according to claim 9 in architectural glass, vehicle window glass, rearview mirror, optical lens or solar photovoltaic field.

Citation Information

Patent Citations

  • Super-hydrophobic surface formed on basis of dihydrazide derivative molecular gel

    CN105858592A

  • High-transparency, super-hydrophobic and rainbow-pattern-free quartz disordered nanostructure as well as preparation method and application thereof

    CN115849295A

  • Fluorine-containing epoxy acrylate polymer, light-cured transparent super-hydrophobic coating and preparation method of fluorine-containing epoxy acrylate polymer and light-cured transparent super-hydrophobic coating

    CN116535585A

  • Nanometer SiO2 super-hydrophobic coating and preparation process and application thereof

    CN110627376A

  • Nano particle / organic gel composite super-hydrophobic coating with self-cleaning property and preparation method of nano particle / organic gel composite super-hydrophobic coating

    CN115537050A